2018
DOI: 10.3390/su10072520
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Land Management, Adaptive Silviculture, and New Forest Challenges: Evidence from a Latitudinal Gradient in Italy

Abstract: Aimed at reducing structural homogeneity and symmetrical competition in even-aged forest stands and enhancing stand structure diversity, the present study contributes to the design and implementation of adaptive silvicultural practices with two objectives: (1) preserving high wood production rates under changing environmental conditions and (2) ensuring key ecological services including carbon sequestration and forest health and vitality over extended stand life-spans. Based on a quantitative analysis of selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
3
0
1
Order By: Relevance
“…For suburban Fagus sylvatica stands, it is demonstrated that the species richness, also the cover and height, of the herb and moss layer is lower in regularly visited forests [110]. Innovative forest management practices compared with traditional thinning result in higher stand productivity along with better structural and functional variables [111]. The data presented in current study allow us to challenge the hypothesis of low species diversity in silviculture stands [17,112].…”
Section: Discussionmentioning
confidence: 64%
“…For suburban Fagus sylvatica stands, it is demonstrated that the species richness, also the cover and height, of the herb and moss layer is lower in regularly visited forests [110]. Innovative forest management practices compared with traditional thinning result in higher stand productivity along with better structural and functional variables [111]. The data presented in current study allow us to challenge the hypothesis of low species diversity in silviculture stands [17,112].…”
Section: Discussionmentioning
confidence: 64%
“…This occurs with beech in its southernmost distribution, where the periodical small-gap creation implies an advantage in the regeneration of beech compared to other species [52]. This is also important to improve silvicultural treatments, as can be reviewed in [53] and [26] where BA is considered one of the most sensitive variables to those treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Глобальне збезлісення і де градація лісів є причиною викидів у середньо му 2,9 млрд тонн двоокису вуглецю на рік, і на глобальному рівні зростає консенсус щодо не обхідності більш ефективного захисту лісів шляхом обліку їх вигод і створення механізмів для оплати їх результатів [2]. Такі глобальні зміни в умовах зростаючих екологічних пору шень вимагають адаптивних підходів до управ ління лісами, що враховують рушії, відгуки та обмежувальні фактори, порівняння спадщини та нових продуктивних критеріїв, перехід від колишнього стійкого стану до більш динаміч ного лісокультурного підходу [3]. 11 березня 2021 року Організація Об'єднаних Націй прий няла нову статистичну базу Ecosystem Accoun ting для кращого обліку біорізноманіття та еко систем у національному економічному плану ванні, що дозволяє країнам використовувати загальний набір правил та методів для відсте ження змін в екосистемах та їх послугах.…”
Section: постановка проблемиunclassified